2023
DOI: 10.1590/1414-431x2023e12364
|View full text |Cite
|
Sign up to set email alerts
|

Association of coronary artery calcium with heart rate variability in the Brazilian Longitudinal Study of Adult Health - ELSA-Brasil

Abstract: Current data shows that the autonomic and vascular systems can influence each other. However, only a few studies have addressed this association in the general population. We aimed to investigate whether heart rate variability (HRV) was associated with coronary artery calcium (CAC) in a cross-sectional analysis of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). We examined baseline data from 3138 participants (aged 35 to 74 years) without previous cardiovascular disease who underwent CAC score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The logistic regression in Table 2 shows that HRV LF predicts CAC+ independently of blood pressure. Hoshi et al [27] found that in participants of age 49 years or older, there is a significant association between HRV LF and CAC regardless of hypertension and other clinical factors, suggesting autonomic neuropathy as a possible cause. Jae et al [28] reported that attenuated HR recovery after exercise was associated with advanced CAC, independent of other hemodynamic confounders.…”
Section: Hrvmentioning
confidence: 99%
“…The logistic regression in Table 2 shows that HRV LF predicts CAC+ independently of blood pressure. Hoshi et al [27] found that in participants of age 49 years or older, there is a significant association between HRV LF and CAC regardless of hypertension and other clinical factors, suggesting autonomic neuropathy as a possible cause. Jae et al [28] reported that attenuated HR recovery after exercise was associated with advanced CAC, independent of other hemodynamic confounders.…”
Section: Hrvmentioning
confidence: 99%